Rencana Keputusan Investasi Truk dengan Metode Capital Budgeting untuk Efisiensi Biaya Operasional: Studi Kasus PT. XYZ - Dafa Rabbani, Raihan; Herlina, Herlina; Yuwono, Istantyo (SURYA TEKNIKA, 2025)
PT. XYZ has problems in supplying large amounts of activated carbon to large companies; so far the company still relies on third-party expedition services to rent trailer trucks for its deliveries. To address this issue, we conducted an investment feasibility analysis using the capital budgeting method for truck procurement. The results of the analysis show that investment in the UD Quester GDE280 Euro 5 truck is feasible. The payback period (PP) was recorded at 3.91 months, the net present value (NPV) was Rp9,581,482,520, and the internal rate of return (IRR) reached 40.66%, far exceeding the minimum attractive rate of return (MARR) of 8.53%. The Profitability Index (PI) was also positive at 13.28%, and operational cost efficiency showed potential savings of 33.31%. Based on these indicators, the investment in truck procurement is not only financially feasible but also able to significantly increase the company's operational efficiency.